2013
DOI: 10.1007/s00267-013-0148-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nutrient Management Planning on Crop Yield, Nitrate Leaching and Sediment Loading in Thomas Brook Watershed

Abstract: Government priorities on provincial Nutrient Management Planning (NMP) programs include improving the program effectiveness for environmental quality protection, and promoting more widespread adoption. Understanding the effect of NMP on both crop yield and key water-quality parameters in agricultural watersheds requires a comprehensive evaluation that takes into consideration important NMP attributes and location-specific farming conditions. This study applied the Soil and Water Assessment Tool (SWAT) to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…However, the results are found to vary significantly and provide important insights only for particular agricultural watersheds (Park et al, 2014;Amon-Armah et al, 2013;Liu et al, 2013;Bosch et al, 2013;Betrie et al, 2011;Lam et al, 2011). Despite the increased use of modeling tools to assess the impact of CT as an agricultural BMP on the pollutant losses, there are still knowledge gaps in this topic.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results are found to vary significantly and provide important insights only for particular agricultural watersheds (Park et al, 2014;Amon-Armah et al, 2013;Liu et al, 2013;Bosch et al, 2013;Betrie et al, 2011;Lam et al, 2011). Despite the increased use of modeling tools to assess the impact of CT as an agricultural BMP on the pollutant losses, there are still knowledge gaps in this topic.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have documented positive effects of NT in reducing NO 3 − concentration in groundwater 4 , 13 , other studies have found no effect 14 , 15 . Many variables, including physical (e.g., rainfall variability, soil texture) and management factors (e.g., crop species, fertilizer type, tillage duration) likely affect NO 3 − mobility and export from agricultural fields 16 . Changes in rainfall intensity, in particular, can influence the amount of NO 3 − carried into the waterways as they affect the amount of water leaving the system 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Variable effects of NT on soil P loss have been reported, likely due to the various physical (e.g., transport pathway, rainfall variability) and management factors (e.g., crop species, tillage duration) affecting P transport in agricultural landscapes (Amon‐Armah et al, 2013). Surface transport primarily consists of runoff, which involves interactions of water with nutrients in the surface soil layers.…”
mentioning
confidence: 99%